A phase 3, randomized, controlled, open-label study to evaluate the persistence up to 5 years of 1 or 2 doses of meningococcal conjugate vaccine MenACWY-TT given with or without 13-valent pneumococcal conjugate vaccine in 12–14-month-old children. Issue 5 (27th January 2023) - Cutland, Clare L.; Peyrani, Paula; Webber, Chris; Newton, Ryan; Cutler, Mark; Perez, John L.
Highlights: We report immune persistence up to 5 y post MenACWY-TT vaccination of 12–14-mo-olds. Immune responses declined over time but were higher at 5 y vs before vaccination. Comparable antibody persistence at Year 5 was observed with 1 or 2 MenACWY-TT doses. Geometric mean titers were elevated in those who received 2 vs 1 dose. No new safety concerns were identified over the study duration. Abstract: Background: Immunogenicity and safety up to 5 years after administration of 1 or 2 doses of quadrivalent meningococcal serogroup A, C, W, and Y tetanus toxoid conjugate vaccine (MenACWY-TT) given alone or with 13-valent pneumococcal conjugate vaccine (PCV13) in children was investigated. Methods: This phase 3 study randomized healthy 12–24-month-olds to MenACWY-TT at Month 0 (ACWY1d), MenACWY-TT at Months 0 and 2 (ACWY2d), MenACWY-TT and PCV13 at Month 0 (Co-Ad), or PCV13 at Month 0 and MenACWY-TT at Month 2 (PCV13/ACWY). Immune responses 1, 3, and 5 years after primary vaccination were evaluated with serum bactericidal activity using rabbit complement (rSBA) titers ≥ 1:8 and geometric mean titers (GMTs). Evaluation of serious adverse events up to 5 years after primary vaccination are reported. Results: Of the 802 children randomized in the study, 619 completed the study through Year 5. Immune responses after vaccination declined over time but were higher 5 years after vaccination compared with levels before vaccination. At Year 5, the percentages of children with rSBA titers ≥ 1:8 across all serogroups were 20.5 %−58.6 %, 28.4 %−65.8 %, 23.9 %−52.8 %, and 19.4 %−55.8 % in the ACWY1d, ACWY2d, Co-Ad, and PCV13/ACWY groups, respectively. Comparable antibody persistence at Year 5 was observed for participants receiving 1 or 2 doses of MenACWY-TT, although GMTs were elevated in those who received 2 versus 1 dose. The percentage of children with protective antibody titers at Year 5 was similar in participants who received PCV13 and MenACWY-TT compared with that observed for participants who only received 1 or 2 MenACWY-TT doses. No new safety concerns were identified during the study period. Conclusion: Antibody responses persisted in the majority of children up to 5 years after primary vaccination with MenACWY-TT administered in a 1- or 2-dose regimen with or without PCV13, with no new safety concerns identified. ClinicalTrials.gov Identifier NCT01939158; EudraCT number 2013–001083-28.